1999
DOI: 10.1074/jbc.274.8.4722
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a Mitochondrial Selenocysteine-containing Thioredoxin Reductase from Rat Liver

Abstract: A thioredoxin reductase (TrxR), named here TrxR2, that did not react with antibodies to the previously identified TrxR (now named TrxR1) was purified from rat liver. Like TrxR1, TrxR2 was a dimeric enzyme containing selenocysteine (Secys) as the COOH-terminal penultimate residue. A cDNA encoding TrxR2 was cloned from rat liver; the open reading frame predicts a polypeptide of 526 amino acids with a COOH-terminal Gly-Cys-Secys-Gly motif provided that an in-frame TGA codon encodes Secys. The 3-untranslated regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
137
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(139 citation statements)
references
References 59 publications
2
137
0
Order By: Relevance
“…It needs selenocysteine as the penultimate amino acid residue for its appropriate enzymatic function (Marcocci et al, 1997;Gromer et al, 1998;Lee et al, 2000;Gorlatov and Stadtman, 2000). Recently, two more tissue-specifically expressed isoenzymes were also identified as selenoproteins (Gasdaska et al, 1999;Lee et al, 1999;Watabe et al, 1999) and related proteins were identified by 'in silico' cloning (Lescure et al, 1999). Various natural and synthetic compounds, apart from disulfide groups in peptides and proteins, can be reduced by TrxR Björnstedt et al, 1995).…”
Section: Metabolic Function Of Mammalian Selenoproteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…It needs selenocysteine as the penultimate amino acid residue for its appropriate enzymatic function (Marcocci et al, 1997;Gromer et al, 1998;Lee et al, 2000;Gorlatov and Stadtman, 2000). Recently, two more tissue-specifically expressed isoenzymes were also identified as selenoproteins (Gasdaska et al, 1999;Lee et al, 1999;Watabe et al, 1999) and related proteins were identified by 'in silico' cloning (Lescure et al, 1999). Various natural and synthetic compounds, apart from disulfide groups in peptides and proteins, can be reduced by TrxR Björnstedt et al, 1995).…”
Section: Metabolic Function Of Mammalian Selenoproteinsmentioning
confidence: 99%
“…By reduction of hydroperoxides to the corresponding alcohols, these enzymes can prevent the production of reactive oxygen radicals and thus may contribute to the protection of the Selenium in Biology 851 Ursini et al, 1982;Brigelius-Flohé et al, 1994 Plasma GPx (pGPx, GPx-3) Takahashi et al, 1987 Gastrointestinal GPx (GI-GPx, GPx-GI, GPx-2) Chu et al, 1993 Iodothyronine deiodinases 5Ј-deiodinase, type I (5ЈDI) Behne et al, 1990;Arthur et al, 1990 5Ј-deiodinase Lee et al, 1999;Watabe et al, 1999;Miranda-Vizuete et al, 1999;Gasdaska et al, 1999 Thioredoxin reductase homologs (SelZf1; SelZf2) Lescure et al, 1999 Selenophosphate synthetase-2 Guimaraes et al, 1996 Functionally undefined 15 kDa selenoprotein of T cells Gladyshev et al, 1998 Selenoprotein P 10 (SelP) Motsenbocker and Tappel organism's macromolecules and biomembranes against oxidation (Sies et al, 1972;Flohé, 1989;Ursini et al, 1995). The role of the cytoplasmic GPx as an 'emergency enzyme' to fight oxidative stress was verified by reverse genetics (Ho et al, 1997;Cheng et al, 1998;de Haan et al, 1998;Fu et al, 1999;Jaeschke et al, 1999) and, in this role, cGPx cannot be substituted by any of the other selenoproteins.…”
Section: Metabolic Function Of Mammalian Selenoproteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…This gene is now known as TR1 (Arner and Holmgren, 2000). Recently, two other TR homologues TR2 and TR3 have been described (Lee et al, 1999;Sun et al, 1999a), which are expressed in a tissue and organelle speci®c manner. However, their speci®c physiologic roles are unclear at this stage.…”
Section: Discussionmentioning
confidence: 99%
“…TrxRs contain an FAD domain, an NADPH-binding domain, an interphase domain, and a penultimate Sec residue in a 16-residue C-terminal extension, which is indispensable for their enzymatic activity (120,216,353,354). Three mammalian TrxR selenoenzymes have been identified: the cytosolic enzyme TrxR1 (301), the mitochondrial enzyme TrxR2 (197,228), and a testis-specific enzyme thioredoxin-glutathione reductase (TGR/TrxR3), the latter also possessing glutathione and glutaredoxin reductase activity (295,296). In addition, alternative splicing events have been reported within these genes (61,83,229,297), suggesting the existence of an even greater variety of TrxR species with different regulation and cellular functions.…”
Section: From Selenium To Selenoproteins 787mentioning
confidence: 99%